2020
DOI: 10.21203/rs.3.rs-15570/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use, awareness and willingness to self-test for HIV: An analysis of cross-sectional population-based surveys in Malawi and Zimbabwe

Abstract: Background Many southern African countries are nearing the global goal to diagnose 90% of people with HIV by 2020. In 2016, 84% and 86% of people with HIV knew their status in Malawi and Zimbabwe respectively. Despite this progress, gaps remain, particularly among men (≥25 years). We investigated awareness, use and willingness to HIV self-test (HIVST) prior to large scale implementation and explored sociodemographic associations. Methods We pooled responses from two of the first cross-sectional Demographic Hea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Our findings are consistent with Johnson et al [10] but show that they are generalizable across nine countries in SSA; countries in this study represent about 40.7% of the HIV epidemic in the SSA region (see Table, SDC 9, http://links.lww.com/QAD/C353) [17,18]. Our findings that these less advantaged groups are also less likely to use HIVST are also similar to a recent single-country study undertaken in rural Malawi [19].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are consistent with Johnson et al [10] but show that they are generalizable across nine countries in SSA; countries in this study represent about 40.7% of the HIV epidemic in the SSA region (see Table, SDC 9, http://links.lww.com/QAD/C353) [17,18]. Our findings that these less advantaged groups are also less likely to use HIVST are also similar to a recent single-country study undertaken in rural Malawi [19].…”
Section: Discussionsupporting
confidence: 94%
“…This initiative started in 2015 with implementation in three SSA countries (Malawi, Zambia, and Zimbabwe), followed by many others, and has resulted in 77 countries introducing policies that promote HIVST as of 2019 [8,9]. However, one study of HIVST awareness and uptake in Zimbabwe and Malawi found low levels of awareness (12.6%) and use (1.2%) [10], despit7e a high willingness to test (84.5%) among Zimbabwean men, the only sub-group in whom willingness was assessed [10]. Aside from this study, relatively little is known about the current levels of HIVST awareness and uptake in much of the region.…”
Section: Introductionmentioning
confidence: 99%
“…While our intervention required additional resources, our study provides proof‐of‐concept that most Kenyan patients are willing to be tested and can be linked to HIV care and partner notification within facilities, provided a system is set up to ensure HIV testing. Offering oral HIV self‐testing to patients presenting with symptoms of acute infectious illness would be one approach to increase feasibility; this strategy has proven effective in settings similar to ours [6,32]. While oral HIV self‐testing would not identify AHI, if applied in our study, it would have identified one chronic HIV infection for every 40 participants tested in the intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges impacting uptake of PITC include logistics, data systems and human resources and management -reflecting the weaknesses of health systems in the region [5]. Most patients are willing to be tested [6,7], but the yield of PITC even in highly endemic areas has recently been estimated at around 1% [3]. Therefore, HIV testing of patients seeking healthcare should be strategic and targeted to increase both the yield and number of newly diagnosed patients.…”
Section: Introductionmentioning
confidence: 99%
“…≥2) partners, homosexual intercourse (asked of men), receipt of gifts, cash, or other compensation in exchange for sex (asked of women), or infection with another sexually transmitted disease. Individuals exposed to any of these factors were classified as “high risk”; the remaining participants were classified as “low risk” if they did not report any sexual activity in the past six weeks, and as “moderate risk” otherwise [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%